2007
DOI: 10.1021/bi701297f
|View full text |Cite
|
Sign up to set email alerts
|

Unusually Strong H-Bonding to the Heme Ligand and Fast Geminate Recombination Dynamics of the Carbon Monoxide Complex of Bacillus subtilis Truncated Hemoglobin

Abstract: The active site of the oxygen-avid truncated hemoglobin from Bacillus subtilis has been characterized by infrared absorption and resonance Raman spectroscopies, and the dynamics of CO rebinding after photolysis has been investigated by picosecond transient absorption spectroscopy. Resonance Raman experiments on the CO bound adduct revealed the presence of two Fe-CO stretching bands at 545 and 520 cm-1, respectively. Accordingly, two C-O stretching bands at 1924 and 1888 cm-1 were observed in infrared absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 36 publications
6
50
1
Order By: Relevance
“…The ∼ 2 ns time constant and the large amplitude (57% of the total absorbance change) of this kinetic phase suggest that the barrier for recombination is low and/or the barrier for escape is high. The geminate recombination in Tf- trHb is similar to that reported for the CO complexes of Bacillus subtilis Bs- trHb [26] and Micobacterium tubercolosis Mt- trHbO [24], [28]. Accordingly, the three proteins ( Tf -trHb, Bs -trHb and Mt -trHbO) exhibit very similar distal heme pocket architecture with highly conserved polar residues.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The ∼ 2 ns time constant and the large amplitude (57% of the total absorbance change) of this kinetic phase suggest that the barrier for recombination is low and/or the barrier for escape is high. The geminate recombination in Tf- trHb is similar to that reported for the CO complexes of Bacillus subtilis Bs- trHb [26] and Micobacterium tubercolosis Mt- trHbO [24], [28]. Accordingly, the three proteins ( Tf -trHb, Bs -trHb and Mt -trHbO) exhibit very similar distal heme pocket architecture with highly conserved polar residues.…”
Section: Discussionsupporting
confidence: 79%
“…Recent works clearly indicated that in Tf -trHb TrpG8 and TyrCD1 are mainly involved in the stabilization of exogenous ligands, namely sulfide [17] or fluoride [21] in the ferric state, and CO in the ferrous state [22]. A similar network of interaction has also been described in Mycobacterium tuberculosis [23][25] and Bacillus subtilis trHbOs [26], [27]. However, information on the dynamic behavior of group II truncated hemoglobins upon CO photolysis is limited to partial observation demonstrating the presence of an efficient and fast geminate recombination process in the picosecond-nanosecond time scale [24][26], [28].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The important role of Trp(109)G8 in ligand stabilization has been observed previously in other TrHbIIs, e.g. Bs-2/2HbO [45,47], Tf-2/2HbO [46] and Mt-2/2HbO [37,44]. No significant interactions of the CO ligand with His(58)CD1 are apparent from the simulations (data not shown).…”
Section: Molecular Dynamics Simulationssupporting
confidence: 73%
“…However, it is qualitatively similar to that of truncated bacterial hemoglobins. 37,38 Analyses of the kinetics of CO dissociation can be used to sensitively probe the heme environment, as demonstrated by experiments on genetically modified proteins. 36,38−41 This is also the case for Af GcHK ( Figure S2).…”
Section: Effect Of Ph On the Autophosphorylation Reactionmentioning
confidence: 99%